Emergency Sleep Medicine - Guay, Christian S.; Ellenbogen, Jeffrey M. (Seminars in Neurology, 2017)
Sleep is a tranquil process that contributes substantially to our overall health and well-being. Yet sleep creates certain vulnerabilities. These sometimes require urgent management decisions for prehospital emergency medical services and on-call medical providers alike. Some of these emergencies may be directly due to sleep itself, whereas others may result from sleep disorders or a lack of sleep. And then some medical emergencies may occur during sleep by chance. Yet for some of these emergencies, sleep does not necessarily play a benign role. Sleep can mask the emergency—causing a delay in detection, confusion in the diagnosis, or even impede treatment. Finally, some disorders will mimic sleep and thus elude detection. Understanding these core principles will enable medical practitioners to optimize care for patients in emergency situations.
Keywords: sleep; emergency medicine; seizures; stroke; sleep–wake disorders